AN EMPIRICAL REVIEW OF SUPPORT SERVICES AND CAREER DECISIONS OF FEMALE STUDENTS IN HIGHER EDUCATION - Ali Raza; Amina Shamsher; Bakhtawar Anwar; Sadia Tahir (Policy Journal of Social Science Review, 2026)
This paper aims to investigate how academic efficacy and support services influence the career decisions of female students in higher education. The career decision-making process is crucial for students in general and for female students in particular at all levels. This study based on a systematic review of the literature and data extracted from reputable databases, including JSTOR, Springer Nature, Sage, Taylor & Francis, Wiley, Emerald Insights, Elsevier, and other reputable databases. Further, the downloaded documents verified from Google Scholar. This study reached the saturation point after reviewing the 85 published documents. Data presented in the results and the discussion sections used to conclude. The study findings reveal that academic efficacy has effects on the career decision-making of female students at higher education levels. Similarly, support services for female students have a similar nature of results to predict career decision-making of female students. The study findings indicate that female role models, parental support, and job security have an effect on the career decision-making process of female students at the higher education level. Keywords: Academic Efficacy, Support Services, Career Decision Making, Higher Education,Female Student